Perlaksanaan TQM : Perancangan Strategik Kualiti dalam Pengurusan Pendidikan - Elias, Haji Abdul Hamid (1998)
The Strategic Quality Planning in TQM has help to change the management paradigm of the corporate sector as well as the public sector. In order to implement this programme more effectively, the Public Service Department has introduced numerous guide-lines for all its departments and public schools to follow. This empirical study will investigate the effectiveness and success of implementing strategic quality planning in the public schools. The targeted research objectives were to; a) broaden the knowledge of strategic quality planning thus supporting its implementation in schools, b) determine which steps (guide-lines) taken are perceived by teachers to be of more importance in the implementation of strategic quality planning in the public schools, and c) check the relationship between the steps (guide-lines) taken in determining the success of implementing strategic quality planning in the public schools. A survey was conducted to get the teacher’s perception in the District of Hilir Perak to clarify the above objectives. The results of the statistical analysis revealed several important findings. First, the continous improvement activities were accepted statistically to be of more importance in implementing strategic quality planning at schools. Second, four out of five hyphotesis proposed were perceived positively by the teachers, Third, two out of the five steps involved; internal analysis and continous improvement activities were found to be more pertinent in compensating the success of implementing strategic quality planning at the public schools. This study shows that not all the steps taken in implementing strategic quality planning is perceive to be of equal importance even though more than three quarter of the respondents supported its implementation. The success and effectiveness of implementing strategic quality planning in schools could have been enhanced if the importance were given prior consideration by teachers.